2011
DOI: 10.1177/103530461102200104
|View full text |Cite
|
Sign up to set email alerts
|

Privatisation and ‘Light-Handed’ Regulation: Sydney Airport

Abstract: This paper examines the privatisation of Sydney Airport and the regime of ‘light-handed’ monitoring of service quality and airport charges that followed the sale in 2002. The arguments for privatisation are reviewed, in particular the need for increased competition and/or appropriate regulation where a former public monopoly, such as Sydney Airport, is sold. The aftermath of the privatisation of the airport has led to complaints by the major airlines and consumers of ever increasing charges for use of the airf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…through equity or corporate bonds) provided a yield of roughly 8 to 12% (Helm and Tindall, 2009: 425). As O'Donnell et al (2011) describe, to pay that level of returns Macquarie Airports borrows against the value of its assets and pays out investors on the basis of debt. Valuation methods are therefore used as another key financial strategy to ensure that the value of their airports is as high as possible.…”
Section: Macquarie: Constructing Brussels Airport As a Financial Assetmentioning
confidence: 99%
See 1 more Smart Citation
“…through equity or corporate bonds) provided a yield of roughly 8 to 12% (Helm and Tindall, 2009: 425). As O'Donnell et al (2011) describe, to pay that level of returns Macquarie Airports borrows against the value of its assets and pays out investors on the basis of debt. Valuation methods are therefore used as another key financial strategy to ensure that the value of their airports is as high as possible.…”
Section: Macquarie: Constructing Brussels Airport As a Financial Assetmentioning
confidence: 99%
“…For Macquarie, gaining control over the finances and operations of the airport through majority ownership is therefore a central element of their investment policy. Macquarie changed the operation of the airport through the adoption of a more commercial and cost efficient policy, placing three managers on-site and implementing a management model similar to that of their other airports (O'Donnell et al, 2011;Solomon, 2009). Initiatives such as progressive labour reduction, real estate development and cost improvement programmes were executed through a transition steering committee with members of Macquarie Airports' staff (Macquarie Airports, 2005: 13-15).…”
Section: Macquarie: Constructing Brussels Airport As a Financial Assetmentioning
confidence: 99%
“…Privatised airports must finance their own operating and infrastructure development costs as well as diversify their revenue sources by relying not only on the revenue derived from aeronautical charges such as landing charges and ground handling services, but also from non-aeronautical sources such as real estate, retailing, and car park facilities (Rowley, 1997;Schulte, 2009). In fact, airports are increasingly pushed to increase revenue and reduce costs which might, incentivise short-term thinking in terms of profit generation (Aulich and Hughes, 2013;O'Donnell et al, 2011), or in contrast lead to the exploration of forming various long-term vertical relationships with downstream airlines to utilize synergy effects (Fu et al, 2011).…”
Section: Airport Pricing Cost and Infrastructure Investmentmentioning
confidence: 99%
“…Forsyth () pointed out some of the complaints of the airlines, as did Thomas (). More specifically, in looking at Sydney Airport, O'Donnell et al () found that gains in efficiency had come at the expense of airlines and other airport customers in the form of higher charges. Employees at the airport had also suffered from the loss of jobs and outsourcing.…”
Section: Industry Sectorsmentioning
confidence: 99%